Practical power system operation - Vaahedi, Ebrahim; Wiley eBooks (Hoboken, New Jersey : IEEE Press/Wiley, 2014)
"An ideal power system operation is the pinnacle of safety, reliability, and efficiency. In Practical Power System Operation, author Ebrahim Vaahedi addresses system operators? viewpoints in handling power system operation issues, a holistic approach that electrical textbooks rarely take. The book covers developments in the energy landscape, energy management systems, and distribution management systems with practical applications that meet architecture and infra-structure requirements. Professional engineers and engineering students at all levels can benefit from an expert?s unique perspective on efficient power systems"--
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Electric power systems -- Management; Operations research; TECHNOLOGY & ENGINEERING / Power Resources / General; Electric power systems -- Management; Operations research; Electronic books